Morphologic and Osteometric Analysis of the Skull of Markhoz Goat (Iranian Angora) - Nader Goodarzi; Toraj Shah Hoseini (Veterinary Medicine International)
This study provides some comprehensive osteometric and morphologic descriptions of the skull region of the Markhoz goat. Totally, 17 osteometric parameters of eight skulls of Markhoz goat were measured and expressed as mean ± SD. A skull length of 18.67 ± 0.66, a cranial length of 11.1±0.38, a facial length of 10.23±0.76, a skull index of 47.77±1.96, a cranial index of 54.04±2.29, a facial index of 100.77±6.85 and a foramen magnum index of 89.32±14.1 were recorded. Morphologically frontal bone did not constitute the caudal extent of frontal surface; rather it was formed by the parietal bone. There were two supraorbital foramina in both sides. The prominent facial tuberosity lies dorsally to the 3rd cheek tooth. The infraorbital foramen was single on either side which was located directly dorsally to the junction of the first and second upper premolar. The orbits were round and complete and located on a frontolateral oblique plane. The basilar part of the occipital bone was surrounded by two pairs of muscular tubercles with similar size. The temporal line was continuous of the temporal crest and ran over the parietal bone. In conclusion, the morphologic and osteometric data of Markhoz goat are comparable to other ruminants.